1997
DOI: 10.1007/s004200050182
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hand-arm vibration exposure among traffic police motorcyclists

Abstract: The aims of this study were (1) to evaluate subjective symptoms in the hand-arm system of all traffic police motorcyclists of a city located in the central part of Japan and (2) to assess their hand-arm vibration exposure associated with traffic police motorcycle riding. The study population consisted of 119 motorcycling traffic policemen and 49 male controls. By means of a questionnaire, information on the occupational history and the presence of subjective symptoms in the hand-arm system of all subjects was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 16 publications
(17 reference statements)
2
22
0
1
Order By: Relevance
“…Additionally, clinical evidence for a CTS was found in nearly 40% of the tested athletes. Mirbod et al (1997) also registered a high incidence of CTS in police officers riding motorcycles. We agree with Mirbod et al (1997) in that motorcycling is likely to affect the median nerve.…”
Section: Perspectivesmentioning
confidence: 93%
See 2 more Smart Citations
“…Additionally, clinical evidence for a CTS was found in nearly 40% of the tested athletes. Mirbod et al (1997) also registered a high incidence of CTS in police officers riding motorcycles. We agree with Mirbod et al (1997) in that motorcycling is likely to affect the median nerve.…”
Section: Perspectivesmentioning
confidence: 93%
“…According to Mirbod et al (1997), exposure to the vibrations of a motorcycle engine for more than 5.5 h/day increases the risk of overuse syndromes in the upper extremity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that such high intensity vibration can be reduced by providing a standard type suspension to the tractor seat. Mirbod et al [4] analyzed the assessment of hand-arm vibration exposure among traffic police motorcyclists with an objective to evaluate subjective symptoms in the hand-arm system of all traffic police motorcyclists of the city located in the central part of Japan. The aim was to assess hand-arm vibration exposure associated with traffic police motorcycle riding.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known on signs and symptoms related to segmental vibration exposure in motorcyclists[11]. …”
Section: Introductionmentioning
confidence: 99%